PRE SERVICE TEACHERS’ PERCEPTION ON THE IMPLEMENTATION OF PROJECT BASED LEARNING IN MATHEMATIC CLASS - Marah Doly Nasution; Ahmad Ahmad; Zulkifley Mohamed (Jurnal Infinity, 2021)
Project-based learning is one of the 21st-century methods that can increase the students' ability to have useful competence in their knowledge, especially in learning mathematic. Hence, the teachers' perception of the implementation of PBL is essential to know. The purpose of this study was to determine student perceptions about the application of project-based learning models. This research is a survey research with a quantitative descriptive approach. The samples used in this study amounted to 63 students of the sixth semester in the Department of Mathematical Education, Muhammadiyah University North Sumatra. The data collection technique used a questionnaire. The data analysis technique consists of quantitative analysis techniques with a statistical approach. The results of this study indicate that: (1) the students' perceptions of the interaction aspects of students and teachers are in the very good category with a mean score of 85.32%. (2) Students' perceptions of motivation / increasing student interest in learning are in the very high category, with an average score of 85.53%. (3) Students' perceptions on the competency aspect of understanding subject matter are in the very good category with an average score of 85.48%. (4) Students' perceptions of the competency aspects of critical, effective, and efficient thinking are in the category of strongly agree with a mean score of 82.62%. (5) Students' perceptions of good time management competence are in the good category with an average score of 79.10%. (6) Students' perceptions of good student learning outcomes are in the very good category, with a mean score of 82.67%. (7) Students' perceptions of the learning model's conformity aspect with subject characteristics are in the very high category with a mean score of 84.05%.